PREPARATION FOR MATHEMATICS OLYMPIADS FOR UNIVERSITY STUDENTS - Nabikhonov Nabikhon Yokubjon ugli (Educational Research in Universal Sciences, 2024)
This article presents a sample mock exam to prepare for Mathematical Olympiads. It presents complex problems and their solutions from fields such as algebra, mathematical analysis, topology, combinatorics, number theory. Necessary for solving given problems, important theorems and affirmations are given. Modern and unusual methods for solving mathematical problems are described. For each problem, a marking scheme is also given that complies with the requirements of International Mathematical Olympiads.